Incidence and outcome after first molecular versus overt recurrence in patients with Philadelphia chromosome–positive acute lymphoblastic leukemia included in the ALL Ph08 trial from the Spanish PETHEMA Group. Issue 16 (23rd April 2019) - Ribera, Josep‐Maria; García, Olga; Moreno, María‐José; Barba, Pere; García‐Cadenas, Irene; Mercadal, Santiago; Montesinos, Pau; Barrios, Manuel; González‐Campos, José; Martínez‐Carballeira, Daniel; Gil, Cristina; Ribera, Jordi; et al.
Abstract : Background: Disease recurrence occurs in 20% to 40% of adults with Philadelphia chromosome–positive acute lymphoblastic leukemia (Ph+ ALL) who are treated with chemotherapy and tyrosine kinase inhibitors (TKIs). In the current study, the authors report the incidence, treatment, and outcome after first disease recurrence in young and older adults treated in the ALL Ph08 trial (ClinicalTrials.gov identifier NCT01491763). Methods: Patients aged 18 to 55 years with de novo Ph+ ALL were treated with imatinib concurrently with standard‐dose induction and consolidation therapy followed by allogeneic hematopoietic stem cell transplantation (allo‐HSCT) when possible. In patients with first disease recurrence, the authors analyzed the type of recurrence, timing, location, presence of kinase domain mutations, type of treatment, and outcomes. Results: Of the 125 patients, 28 patients (22%) developed disease recurrence before (4 patients) or after (24 patients) HSCT, with the recurrences being molecular in 11 patients (39%) and overt in 17 patients (61%). T315I was the most common mutation noted at the time of disease recurrence. Change in TKI was the most frequent treatment for patients with molecular disease recurrence whereas rescue chemotherapy and TKI change followed by second allo‐HSCT when possible were performed for the most part in patients with overt disease recurrence. A total of 20 patients (71%) achieved response. The median disease‐free survival (DFS) and overall survival (OS) were 8.5 months and 15.3 months, respectively. A trend for better DFS and OS was observed in patients with molecular recurrence compared with those with overt recurrence (median of 16.9 months vs 6.3 months [ P = .05] and 28.7 months vs 11.5 months [ P = .05] for DFS and OS, respectively). Conclusions: Disease recurrence was frequent in young and older adults with Ph+ ALL who were treated with imatinib and chemotherapy with HSCT. Although the majority of patients responded to rescue therapy, their outcomes were poor, especially with regard to overt disease recurrence. Abstract : Outcomes after first disease recurrence in adults with Philadelphia chromosome–positive acute lymphoblastic leukemia are poor. Patients with overt disease recurrence appear to have a worse prognosis compared with those with molecular recurrence.